STUDENTS’ PERCEPTION ON THE USE OF ENGLISH TALK SHOW VIDEO IN THE STUDENTS’ SPEAKING SKILL - Risnawati; Andi Anto Patak; Nurming Saleh (International Journal of Business English and Communication, 2025)
This study aims to identify the extent of students' speaking ability in English and to find out what are the speaking challenges faced by students in communicating by using talk shows as one of the learning media. This research uses qualitative methods as the method used to obtain data from respondents. Data collection techniques used for interviews and audio recording. The result of this study shows that the use of talk show video affects students' speaking ability, vocabulary processing and the application of speaking techniques. As for the speaking challenges, the difficulties that students face in communicating are the use of high language, fast pronunciation and the application of new vocabulary in conversation.